DEPENDENCE OF THE GENERATED POWER ON THE OPERATING MODES OF THE WIND ELECTRIC GENERATOR AS PART OF THE MULTIFUNCTIONAL ENERGY COMPLEX - Kalimbetov Ғ.П.; Toigozhinova А. Ж. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
The wind energy utilization factor (Betz-Zhukovsky criterion) depends on the loss of wind speed when it passes through the plane of the wind wheel. The power generated by the wind turbine differs from the power developed by the wind wheel by the amount of losses when converting the recovered wind energy into useful energy. The choice of wind turbine power is determined by the electrical load of electrical consumers that are used in the facility under consideration. It should be borne in mind that they almost never turn on at the same time. Therefore, the calculation is carried out according to the average indicators of power consumption. The work involves the operation of wind turbines without limiting the carrying capacity. A similar system is used when a wind turbine is operating in the network or in the presence of technical devices for exceeding the power. The revealed effect of automatic stabilization of the electromechanical system in the optimal mode is undoubtedly one of the important advantages of the WPP concept. The simulation results can be used to optimize the control of wind turbines in cluster mode.